Sorption behavior of Cr(VI) on pineapple-peel-derived biochar and the influence of coexisting pyrene. (July 2016) - Wang, Chuanhua; Gu, Lingfeng; Liu, Xiaoyan; Zhang, Xinying; Cao, Liya; Hu, Xiaoxin
Abstract: The influence of pyrolytic temperatures and of the properties of pineapple-peel-derived biochar (PABC) on Cr(VI) sorption behavior with and without pyrene was investigated. The structural characteristics of PABC were analyzed by scanning electron microscopy (SEM), and the surface groups of PABC were analyzed before and after Cr(VI) sorption, using Fourier transform infrared spectroscopy (FTIR). The results indicate that the characteristics of PABC depend on the pyrolytic temperature, and the adsorption isotherms fit well with the Freundlich equation. The greatest sorption capacity, 7.44 mg g −1, occurred with PABC pyrolyzed at 750 °C for 2 h. In addition, the slow sorption kinetics fit well with second-order reaction kinetics. When pyrene coexisted in the solution, the adsorption of Cr(VI) was inhibited because of the inner complex between the hydroxyl groups on PABC and pyrene flushbonading the H bond with Cr(VI). There were no significant changes in the functional groups of the biochar surface between the two sides of the adsorption equilibrium, which demonstrates the slight contribution of organic matter in chromium adsorption. PABC has the potential to remove Cr(VI), but the presence of pyrene can inhibit Cr(VI) adsorption. Highlights: Pineapple peel derived biochar is a good sorbent for removing hexavalent chromium. Pyrolytic temperatures significantly impacted the adsorption capacity. Surface functional groups of the biochar contribute weakly to adsorption. The coexisting pyrene suppresses the hexavalent chromium adsorption on PABCs partly.